Uji Efektifitas Ekstrak Buah Nanas (Ananas Comosus L ) Terhadap Pertumbuhan Dermatofita Pada Pasien Tinea Corporis Secara In Vitro - Abdul Razak; Melviana Lubis (JURNAL PANDU HUSADA, 2020)
Abstract: Fungal infections are the most common disease in tropical and developingcountries. Fungal infections caused by dermatophytes such as Tricophyton. Many plants can be used as traditional medicine, one of which is pineapple (Ananas comosus L.). This study aims to study the benefits of pineapple extract (Ananas comosus L.) on the growth of dermatophytic fungi in tinea corporis in vitro. The type of research conducted is experimental research by making post test only the design of the control group consisting of 4 groups, namely 2 training groups and 2 control groups. The treatment group consists of P1 and P2. each of the oncentration groups is pineapple extract (Ananas comosus L.) with a concentration of 10% and 25%. The control group consisted of P3 as a positive control group (Fluconazole) for Dermatophytes in Tinea corporis and P4 patients as negative controls (aquades). The technique used to measure antifungal activity is the disc diffusion method. The results of research on pineapple extract (Ananas comosus L.) at concentrations of 10%, 25%, flukonazole and aquadest did not produce clear zones. Pineapple fruit extract cannot inhibit the growth of dermatophytes in tinea corporis patients.Keywords: Pineapple Fruit (Ananas comosus L.), Dermatofita, Tinea corporis.